2022
DOI: 10.1186/s13756-022-01058-2
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with hand disinfection in the surgical area of an orthopedic university clinic: results of an observational study

Abstract: Background Hand hygiene using alcoholic hand rub solution is essential for the prevention of surgical site infections. There are several opportunities for hygienic hand disinfection (termed “hand hygiene” in the following) during immediate pre-, intra- and postoperative orthopedic patient care. However, the level of hand hygiene compliance among surgical and anesthesia staff in this context is unclear. Therefore, we conducted an observational study in operating theatres of an orthopedic univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
7
0
1
Order By: Relevance
“…While that study involved university students in different disciplines rather than health care workers, it does support the importance of further research to elucidate whether physicians' overestimation of their hand hygiene is truly a question of motivated social desirability and impression management, or not, more simply, an indication that they may not be aware of what they do in this regard. The fact that explorative analyses revealed that the contrast between the singleitem-based results and the WHO-5-based results was confined to orthopedic/trauma surgeons is consistent with earlier research [34], but further scrutiny regarding differences related to physicians' specialties is needed.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…While that study involved university students in different disciplines rather than health care workers, it does support the importance of further research to elucidate whether physicians' overestimation of their hand hygiene is truly a question of motivated social desirability and impression management, or not, more simply, an indication that they may not be aware of what they do in this regard. The fact that explorative analyses revealed that the contrast between the singleitem-based results and the WHO-5-based results was confined to orthopedic/trauma surgeons is consistent with earlier research [34], but further scrutiny regarding differences related to physicians' specialties is needed.…”
Section: Discussionsupporting
confidence: 74%
“…This is lower than the global average response rate of 53% reported for surgical doctors [35]). However, indirect approaches such as that used in the present survey (i.e., distributing a written questionnaire from the WACH team to the survey respondents via the in-house IPC-teams) were not reviewed in [34]. It is probable that the lack of monetary or similar incentives, lack of personalization of the questionnaire, and the relative length of the questionnaire [36] affected the response rate in the WACH-survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding HHC in the OT, Paul et al reported HHC of 1.4% pre-implementation and 37.9% 60 days post-implementation of an intervention in a universityaffiliated hospital in the USA [9]. In comparison, baseline HHC of 10% was observed at a university hospital in Aachen, HHC of 40.8% was reported in a university hospital in Germany, and overall HHC of 18% was reported in a large academic centre in Virginia [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described different methods to observe HHC in the OT as consensus-based protocols have not been published to date in the international literature. Most studies still use WHO's Five Moments [5,7,10,11,13], but in some studies, HHC has been investigated using survey data on self-reported compliance, completed by OT personnel [6,14]. Nonetheless, adequate hand hygiene in the OT by nonsterile HCWs and surgeons (performing non-sterile actions) is of utmost importance to prevent postoperative wound infections.…”
Section: Introductionmentioning
confidence: 99%